CRISIS MANAGEMENT OF LOCAL GOVERNMENT PUBLIC RELATION (CASE STUDY ON IMAGE RECOVERY OF LOCAL GOVERNMENT KARAWANG REGENCY POST CORRUPTION CASE OF THE REGENT OF 2014) - Laelatul Pathia (Jurnal Ilmiah Publipreneur, 2019)
ABSTRACT    Negative issues the arise in public become one determinant of the continuity of an institution. Institutions will gain more value if they can manage the issues into opportunities, but it can also be a threat if they can not prevent the onset of crisis symptoms. Post-operation catching hands conducted KPK to the head of the region, Ade Swara, and wife, Mrs. Nurlatifah in 2014 experienced a crisis of confidence from the community of Kabupaten Karawang. This study will use the management crisis Rhenald Kasali’s, agenda building strategy, dan media relations activities, and describe how the onset of this crisis emerged, the factors causing, and the anatomy of crisis. Prevention of the crisis should be sought so that the institution is able to restore the trust of the community. The appoinment of Mrs. Cellica as Acting Officer of the Regent has been one of the efforts to restore the crisis, because the institution has regained the leadership capable of providing policies for the institutions existance. The results showed that the crisis that occured in Karawang regency is a type of smoldering crisis, where the crisis is not common in the institution. In the process of disseminating information, PR do some media relations activities so that people get the informations related to the case. In addition, the researches also describe the pattern of institutions conducted on the media